Clinical validation of the Aarhus Side effect Assessment Questionnaire(ASAQ). (April 2022) - Kølbæk, Pernille; Thorgaard, Mette Viller; Grooss, Amalie Schnegelsberg; Selvanathan, Thusitha; Larsen, Sofie Fly; Speed, Maria; Dines, David; Østergaard, Søren Dinesen
Background: Psychotropic medications are essential in the treatment of mental illness. Unfortunately, these medications are associated with side effects that may reduce adherence to treatment and quality of life. Therefore, systematic screening for side effects is fundamental to optimize treatment with psychotropic medications. Self-report of side effects is a practical alternative to time-consuming clinical assessments. We developed the Aarhus Side effect Assessment Questionnaire (ASAQ) in an attempt to strike the balance between extensive coverage of side effects and reasonable application time. Aim: The aim of the study was to validate the ASAQ using the clinician-rated Udvalg for Kliniske Undersøgelser (UKU) Side Effect Scale as gold standard reference. Methods: A total of 122 inpatients and outpatients—mainly with psychotic (39%) and affective disorders (43%)—receiving treatment with psychotropic medication completed the ASAQ and the World Health Organization–Five Well-Being Index (WHO-5) and were subsequently rated on the UKU by trained raters. Results: Using the UKU as the gold standard reference, the ASAQ demonstrated sensitivity values >75% for 77% of its 30 items (ranging from 37% for cutaneous disturbances to 98% for increased sweating) and specificity values >75% for 47% of its 30 items (ranging from 28% for reduced sleep to 98% for micturition disturbances). While 17% of the participants considered discontinuing their medication, 24% had recently refrained from taking their medication as prescribed. A negative correlation was found between the ASAQ and the WHO-5 and total scores (Pearson's correlation coefficient = –0.44). Conclusions: The self-reported ASAQ seems to be a sensitive tool for detecting side effects of psychotropic medications.